A cluster of adenovirus type B55 infection in a neurosurgical inpatient department of a general hospital in Guangdong, China. Issue 4 (26th June 2017) - Yi, Lina; Zou, LiRong; Lu, Jing; Kang, Min; Song, Yingchao; Su, Juan; Zhang, Xin; Liang, LiJun; Ni, HanZhong; Ke, Changwen; Wu, Jie
Abstract : Background: Human adenovirus type 55 is a re‐emerging human respiratory pathogen that is associated with several respiratory infections outbreaks in military and school populations. In this study, we describe the first HAdV55‐associated hospital outbreak documented in Guangdong, China. Methods: Active surveillance was conducted in the involved neurosurgical inpatient department. All staff and patients in the involved neurosurgical department were surveyed for any symptoms of fever (≥38°C) and enlarged tonsils during the outbreak period. Throat swabs and demographic information were collected for all cases. For each specimen, assays for common respiratory viruses were performed using one‐step reverse transcription‐polymerase chain reaction. HAdV‐positive samples were inoculated onto Hep‐2 cells for isolation. Hexon genes, fiber genes, penton genes, and whole genomes were sequenced. A phylogenetic tree was constructed. Results and Conclusions: Forty‐three cases, including 24 laboratory‐confirmed cases and 19 possible cases, were identified. Nurses had the highest attack rate of infection, with a rate of 36.4%. The attack rate for doctors and inpatients was 20.0% and 16.7%, respectively. HAdV55 was the sole pathogen identified during this outbreak. The hexon, fiber, and penton genes from seven isolated HAdV55 stains were sequenced. All these genes showed 100% homology and fell into the HAdV55 [P14H11F14] cluster, indicating that HAdV55 was the single viral strain for the outbreak. While not conclusive, the epidemic investigation revealed that the outbreak was introduced by nurses from sources outside the hospital. It was likely that a transmission from staff to inpatients had occurred.